Efforts to Improve PJOK Learning Outcomes Using the Learning Differentiation Approach of SDN Babatan 1/456 Surabaya - Hasan, Nuuri; Dinata, Vega Candra; Wijayanto, Benny (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
This research aims to improve the learning outcomes of grade VI students at SDN Babatan 1/456 Surabaya in PJOK football material through differentiated learning. The study uses the Classroom Action Research (PTK) method with two cycles based on the Kemmis & McTaggart spiral model, consisting of planning, acting, observing, and reflecting. A total of 25 students participated, with data collected using practice tests assessing kicking skills through indicators of initial, implementation, and final attitudes. Initial observations revealed that only 40% of students achieved mastery, while 60% did not. In the first cycle, the results improved to 68% mastery, leaving 32% incomplete. By the second cycle, the mastery rate increased significantly to 88%, with only 12% remaining incomplete. These findings demonstrate that applying a differentiation approach effectively enhances student learning outcomes in PJOK, particularly in football skills